PELATIHAN PENYUSUNAN PROGRAM PEMBELAJARAN PENDIDIKAN KARAKTER ANAK USIA DINI PADA GURU TK - Mazia Amalia; Wisjnu Martani (HUMANITAS: Indonesian Psychological Journal, 2013)
AbstractThe key of the successful character education program are teachers, school employees and all the school environment because the focus of the character education is the school culture especially kindergarten children who are at the early stage of education. The accomplishment of character education at school is impeded the teachers who are have not understood on how to integrate it into school subjects. The purpose of this research isto test the training of My Plan My Success in improving kindergarten teacher’s ability toward the arrangement of the learning program for character education in young children. This research involved 36 teachers which were divided into experimental (18 teachers) and control (18 teachers) group, using experimental design: untreated control group design with dependent pretest and posttes samples using switching replication. The result of the data analysis that uses analysis data methode namely mixed anova shows there is different ability in the arrangement of learning program for character education in young children significantly (F=8,576; p<0,01). The training gives the effective contribution to experimental group as much as 61,7%. The ability of the,arrangement of learning program forcharacter education in young children in the experimental group is improving (MD=-6,824; p<0,01), after getting intervention. As well as the control group, after getting intervention, there ability is getting improve (MD=-5,765; p<0,00).Keywords : learning program for character education in young children, preschool teacher training.